Enhancing Design Ideation in Traditional Arabian Gulf Artifacts Through the Integration of Contemporary Three-Dimensional Manufacturing Methods (Al-Academy, 2026)
The contemporary designer analyzes and studies the elements of artistic heritage, to identify the intellectual and aesthetic premises that lie in its structure, its elements, its vocabulary, and its encapsulation. With the aim of enriching the design thinking and its sources for the designer and raising the level of creativity and the overall idea of the two- and three-dimensional work, to design artistic models that are original and contemporary, enriching the language of communication between heritage and contemporary.In this way, the heritage and its elements are inspired by a special stylistic display of heritage and its elements in innovative modernist formulations that deviate from the prevailing through its holistic images. And its presentation of elements or processes connected to each other and not as separate parts, to present it in a comprehensive form that supports the opportunities for selection and innovation that stems from it. In addition to those works in which some artists and designers deliberately elevated nature and its elements, drawing inspiration from its elements (human, plant, animal). And simulating them as a basis for artistic formulation, another group of designers sided with drawing inspiration from the elements of Arab heritage, especially in the traditional Arab Gulf artifacts. As a source for enriching the architecture of 2D and 3D designs, And the design of modern models based on the reading comprehension of the philosophical, aesthetic, and structural dimensions of the elements of that heritage.Increasingly traditional crafts of the gulf region are becoming obsolete because of dwindling numbers of traditional craftsmen and cheap imports from Pakistan and Morocco. There is a need to preserve traditional artefacts in the face of this issue.This research assesses the viability of preserving the traditional Arab Gulf artifacts Using modern 3D manufacturing techniques added to maintain Traditional attributes of the original artifact. The methodology included consideration of requirements based on functionality, aesthetics and traditional elements, and the viability of techniques of such requirements in addition to practical and cost considerations. Where the study seeks to provide inputs and examines the intellectual and aesthetic premises of the elements of heritage arts, especially the creative and aesthetic arts. In the artistic artifacts in the heritage Arab Gulf region of an artistic, aesthetic, and structural nature, with richness and diversity in the formal and structural forms of traditional Arab Gulf metal products. As daily life tools such as jugs, trays, incense burners, candlesticks, bowls, cans, dallahs, irons, mirrors, and other metallic artifacts, which represents a fertile source of inspiration, and fertilizes the imagination of the Arab designer to put forward contemporary Arab visions and proposals to enrich design thinking in traditional Arab and Gulf handicrafts and recycling daily life products.And the analytical study of the methods of forming technical design products, their forms and design construction, the materials through which they were designed and formulated, the traditional and new molding methods and techniques, the manufacturing materials, and the surface decorations and textures that dealt with the design plane. To raise the level of creativity and idea, to be inspired by heritage through a special style Heritage and its elements are presented in innovative modernist formulations.